A novel application of triple oxygen isotope ratios of speleothems. (1st February 2020) - Sha, Lijuan; Mahata, Sasadhar; Duan, Pengzhen; Luz, Boaz; Zhang, Pu; Baker, Jonathan; Zong, Baoyun; Ning, Youfeng; Brahim, Yassine Ait; Zhang, Haiwei; Edwards, R. Lawrence; Cheng, Hai
Abstract: We present triple oxygen isotope data from speleothems obtained by an O2 -CO2 Pt-catalyzed oxygen-isotope equilibration method. The high precision (9 per meg or better, 1σ SD) of our new speleothem Δ 17 O (carbonate 17 O anomaly) data is sufficient to resolve subtle hydroclimatic signals. In addition, we determined triple oxygen isotope fractionation factors through two sets of modern paired carbonate-dripwater samples collected at a temperature of 17 ± 1 °C, which is prerequisite to the calculation of triple oxygen isotope compositions of parent meteoric waters at cave sites from speleothem proxy data. Based on this calibration, we back calculated triple oxygen isotope compositions of parent waters across well-characterized climate transitions using speleothem proxy data from three regions. Resulting oxygen-isotope data closely track the Global Meteoric Water Line (GMWL), providing a preliminary validation of the method. Our speleothem Δ 17 O data indicate a 21 per meg difference between Marine Isotope Stage 5d and 5e in samples from Central Asia and a 15 per meg difference between the Middle Holocene and Last Glacial Maximum in samples from the eastern Mediterranean, suggesting a shift in moisture source and/or fractionation history. Unexpectedly, there were no measurable Δ 17 O differences between glacial and interglacial samples from both the South American (western Amazon) and Asian (southern China) monsoon domains, implying consistent moisture-source conditions across glacial and interglacial cycles, at least in terms of relative humidity. Remarkably, Δ 17 O values from the western Amazonian samples are significantly higher (∼20 per meg) than those from Asian monsoon regions, suggesting lower relative humidity along moisture trajectories in the western Amazon during the Middle Holocene and Last Glacial period. Similarly, Δ 17 O values of the eastern Mediterranean samples are significantly higher (19–55 per meg) than those of coeval samples from Central Asia, implying different hydrological environments or moisture sources despite being in the same westerly circulation domain. Speleothem Δ 17 O data may thus provide new and important constraints for understanding regional and global hydroclimate dynamics.